STRES KERJA DAN KETEGANGAN PSIKOLOGIS SEBAGAI PREDIKTOR TERHADAP KEPUASAN KERJA KARYAWAN - Wijono, Sutarto (Noetic Psychology, 2011)
The aim of research was found out job stress and psychological tension as the predictor to job satisfaction people in company of Central Java. Subjects consisted of 93 people of companies in Central Java, Indonesia. AÃÂ  job related tension index by Wolfe, Quinn, Snoek and Rosental (Mustapha, 1994) was used to assess job stress.ÃÂ  A psychological tension questionnaire by Caplan, Cobb, and French (Brief et al, 1981) used to assess psychological tension.Validity coefficient of job stress was 0,333 Ã¢â¬â 0,589 and reliabilility coefficient was 0,828; validity coefficient of psychological tension was 0,357 Ã¢â¬â 0,630 and reliability coefficient was 0,765; validity coefficient of job satisfaction was 0,302 Ã¢â¬â 0,602 and reliability coefficient was 0,808. The statistical methods used multiple regression. The result obtained R = 0.407 with F = 8,931 and p = 0,000 < 0,01; indicate that there are significant effects together ofÃÂ  job stressÃÂ  and psychological tension as the predictor to job satisfaction. Keywords: job stres, psychological tension, and job satisfaction people in companyÃÂ